(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The Purpose of this research is analysis and discussion " The Effect of Insurace Company Capital Adequacy in it’s Profitafility: An Empirical Study compared the two insurance (national, Iraqi), for a period of one year (2005) and the year (2014), as it is framed theoretical side for two topics head adequacy money the insurance company, and the profitability of the insurance company, and I’ve been using the research methodology and analytical, in the analysis and measurement of the capital of the insurance company adequacy, and profitability of the company, as the capital adequacy ratio was measured by dividing the total capital available on the total capital rate risk, after measured and appreciated in two insurance research, while I use to measure the profitability of the financial ratios insurance company index (the percentage return on capital available, the ratio of net profit to sales), through the analysis of financial statements of the two companies the field of research, and available from the balance sheet, and final accounts , financial reports, and for the purpose of evaluate and measure the variables of research, analysis correlation and impact between the two, since I use the analysis of variance ANOVA to measure the correlation and impact between the capital adequacy of the results and the profitability index, this study found and through the discussion of the results of the statistical analysis of a relationship link, and the impact of adverse statistically significant morale among capital adequacy, and profitability in the national insurance company, meaning that the high value of capital unit adequacy ratio of one leads to lower profitability by (0.003), and this is what validates second hypothesis in this current study, which It states that the capital an insurance company adequacy linked and influenced significantly in the profitability of the company, did not prove the hypothesis search in the Iraqi general insurance company, because the moral value of her sig was equal to (0.112), which is greater than the level of significance value (5%), the reason being the presence of anomalous data in the Iraqi insurance company data